Construction and Ion-Beam Characterization of Nuclear Targets - Lykiardopoulou, M.; Tsampa, K.; Mertzimekis, T. J. (HNPS Advances in Nuclear Physics, 2019)
We report on the construction and ion-beam characterization of nuclear targets and thin films as part of the ongoing NuSTRAP group research program at the University of Athens. Two different techniques were used for the preparation of new targets, depending on the desired material and thickness. Self-supported, natural silver targets were manufactured by Physical Evaporation Deposition (PVD) through electrical resistance heating, using the evaporation apparatus at the INPP (NCSR “Demokritos”). Thick iron targets were constructed using the rolling technique at the INRASTES (NCSR “Demokritos”) facilities. The Rutherford Backscattering Spectrometry (RBS) was employed to characterize the newly manufactured and existing targets using proton and deuteron beams accelerated by the Tandem Van de Graff Accelerator (at INPP) at several energies. The results from the analysis of experimental spectra and corresponding simulations carried out with the simNRA software package are presented.